Using critical and post-critical pedagogies to pick at the seams of patriarchy from 'the inside'. Issue 3 (4th May 2017) - Lennon, Sherilyn
ABSTRACT: This article explores the use of critical and post-critical pedagogies in a rural Australian high school for the purposes of unsettling life-limiting gender beliefs and practices. The paper problematises two examples whereby site-specific knowledges, curriculum dictates, media texts and critical pedagogies were enmeshed to create politically charged spaces for re-seeing, re-thinking and re-doing gender. The first example involves a unit of work in which students were required to critically analyse and evaluate a well-known Australian documentary film for the particular version of hypermasculinity that it was valorising. The second example involves the collaborative critiquing of a well-known local text. At the conclusion of the paper, I turn a critically reflexive eye upon myself as a way of considering the ethics and issues for educators of challenging power asymmetries from 'the inside'. It is at this point that I discover it is possibly I who have been disrupted most of all.